Zakat dan Pajak sebagai Lembaga Keuangan Publik - Fitri Fadhilah; Muhammad Viky; Kelvin Putri Sabrina; Sri Devi Septyani; Mohammad Ridwan; Altus salembudi P (Syntax Corporation Indonesia, 2024)
Integration of zakat and tax as public financial institutions. Zakat and tax have different purposes and functions, but both have an important role in national financial management. However, there are problems in the management of zakat and tax, such as inconsistency and lack of public understanding of the difference between zakat and tax. To overcome these problems, steps are needed such as raising public awareness about the difference between zakat and tax through education and awareness campaigns. In addition, it is also important to raise the awareness of the government and financial institutions about the difference between zakat and tax through training and education. Analysis of zakat and tax integration can be done through theoretical, empirical, and qualitative approaches. Through this analysis, effective solutions can be found to overcome the problems of zakat and tax integration, such as strengthening education and socialization, harmonizing regulations, and increasing transparency and accountability in the management of zakat and taxes. With the implementation of the right solution, it is expected that the integration of zakat and tax can provide benefits for individuals, society, and the state. Zakat can help improve the welfare of disadvantaged communities, while taxes can be a source of funding for national development. In order to realize effective integration, it is necessary to have cooperation and synergy between the government, zakat institutions, and the community.